The infant industry argument: Tariffs, NTMs and innovation - Igor Bagayev; Ronald B. Davies (University College Dublin, UCD School of Economics, 2017)
One rationale for the infant industry argument is that, by protecting domestic firms from foreign competition, this increases rents and investment in innovation and other growth enhancing measures. Using data on 4,750 firms across 13 developing countries, we examine whether protection via tariffs or non-tariff measures (SPS and TBT specifically) increase innovation in either products or processes. We find no such evidence; instead we find a small negative impact of protection, particularly tariffs and TBTs, on innovation.
Keywords: F13; H57; F12; 330; Non-Tariff Measures; Technical Barriers to Trade; Innovation; Infant Industry